Fearing the wurst: Robust approach bias towards non-vegetarian food images in a sample of young female vegetarian eaters. (1st June 2020) - Knight, Helen C.; Mowat, Sarah L.; Hesse, Constanze
Abstract: Previous studies have shown that humans show an implicit approach bias toward food related items which is moderated by hunger and properties of the food items displayed (such as their palatability and calorie content). However, little is known about if and how this approach bias is moderated by food preferences and/or diet choices. In this study, we compared approach-avoidance biases in a group of young female omnivore and vegetarian eaters towards images of vegetarian and non-vegetarian food items using a manikin stimulus-response compatibility task. While vegetarian eaters showed a slightly larger approach bias for vegetarian than for non-vegetarian food stimuli, this bias was of similar size to that observed in the omnivorous group. Most interestingly, vegetarian eaters' approach bias towards non-vegetarian food pictures also did not differ from that of the omnivorous group, despite vegetarians rating those pictures as much less pleasant. Our findings suggest that approach biases towards food items are quite robust and do not rapidly change with dietary practice. However, despite approach biases often guiding behaviour, vegetarian eaters successfully withstand these implicit action tendencies and avoid non-vegetarian produce. Potential implications of this finding for the addiction literature are discussed.